EXPERIMENTAL STUDY OF PROFESSIONAL DEVELOPMENT OF FUTURE TEACHERS OF LABOR EDUCATION AND TECHNOLOGIES IN THE PROCESS OF INDEPENDENT WORK - Tsisaruk I. V. (International Journal of Innovative Technologies in Social Science, 2020)
As a result of experimental research, pedagogical modeling of the process of professional development of future teachers of labor education and technology in the process of independent work was carried out. A structural-functional model and an interactive development program are proposed, the implementation of which was carried out at the personal-motivational, innovation-enriching, reflexive-activity and result-diagnostic stages. At the ascertaining stage of the research the state of levels (initial, average, sufficient, high) of professional development of future teachers of labor training and technologies was determined according to certain criteria (value-motivational, cognitive-technological, operational-activity, evaluation-reflexive). The formative experiment and implementation of the interactive development program of the study were conducted in four stages: personal-motivational stage (provided motivated immersion of future teachers of labor training and technology in cooperation and partnership in the process of independent work technologies to develop awareness of the need for continuous professional development). the process of group and individual educational and professional activities in order to develop a lasting interest in the future profession, acquaintance with modern technologies and techniques of technological education in order to motivate to acquire systematic pedagogical knowledge, personal and professional growth); innovation and enrichment stage (provided enrichment with knowledge of new technologies and the ability to apply them in educational and professional activities with a projection on the future profession; contributed to the development of project-technological readiness and ability to enrich strategies of independent work in personal and professional development); reflexive-activity stage (contributed to the development of skills and abilities of group work, creative abilities of future teachers of labor training and technologies in practical activities with the use of innovative forms of organization of the educational process); effective diagnostic stage (provided the use of methods of self-assessment and self-analysis, reflective exercises and training tasks for the future teacher to evaluate the labor education and technologies of his own activity and himself as an individual; formation of their needs and motives for self-knowledge; increasing the level of self-esteem, self-approval in the process of effective independent work). At the control stage, the results of an experimental study were obtained, which confirm the effectiveness of the proposed methods.